2019
DOI: 10.1039/c9qi00849g
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of organic and inorganic impurities into the lattice of metastable vaterite

Abstract: Highly substituted Mg-vaterite and Ba-vaterite were synthesized in the presence of aspartic acid and characterized by means of synchrotron XRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…[20] Many of these protein mixtures have been tested in vitro for their abilityt oi nhibitt he precipitation of CaCO 3 , [10] or to modify the size and morphologyo fc alcite crystals. [21] More surprisingly, proteins, [22,23] or their most elementary building blocks, amino acids, [24][25][26][27] were found to induce anisotropic lattice distortions in their calcitic, aragonitic, or vateritic crystalline hosts. Several synthetic assays also showedt hat other molecules can be incorporated into calcite, such as gels, [28,29] diblock copolymer particles, [30] and manym ore.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Many of these protein mixtures have been tested in vitro for their abilityt oi nhibitt he precipitation of CaCO 3 , [10] or to modify the size and morphologyo fc alcite crystals. [21] More surprisingly, proteins, [22,23] or their most elementary building blocks, amino acids, [24][25][26][27] were found to induce anisotropic lattice distortions in their calcitic, aragonitic, or vateritic crystalline hosts. Several synthetic assays also showedt hat other molecules can be incorporated into calcite, such as gels, [28,29] diblock copolymer particles, [30] and manym ore.…”
Section: Introductionmentioning
confidence: 99%
“…It forms by interaction between additives and calcium or carbonate ions, which lowers the concentration of free ions, thus inducing the formation of vaterite. ,, Slow nucleation rates delay the formation of the more stable polymorphs (aragonite and calcite), so that vaterite can form . Indeed, vaterite crystals were successfully synthesized by using additives containing charged groups such as amines, carboxyl groups, , sulfonic groups, , amino acids, , peptides, polyols, , and proteins. , Vaterite crystals have been synthesized in aqueous solutions, ,,,,, alcohol–water mixed solvents, ,,, DMF–water mixed solvents, , and nonaqueous solvents. ,, Wetting and hydration of ions in alcohol–water solvents are very different from those found in aqueous solutions, which may affect the formation of nucleation and crystal growth centers. The low solubility and high supersaturation of CaCO 3 in alcohols are in favor of the formation of kinetic products (thermodynamically unstable phases such as vaterite).…”
Section: Introductionmentioning
confidence: 99%
“…Figure presents the resulting HR-SEM micrographs. Without any additives, the crystals exhibit the characteristic rhombohedral morphology of calcite. ,, When nucleotides are added, the spherical morphology of vaterite appears in the shape of the crystals . Furthermore, employing energy-dispersive spectroscopy (EDS) in the SEM confirmed that P atoms can indeed be detected within the vaterite crystals (Figure S8).…”
Section: Resultsmentioning
confidence: 86%
“…The field of bio-inspired crystal growth encompasses research that aims at developing novel materials using strategies found in Nature. , In the realm of CaCO 3 , efforts were made to understand the impact of various crystallization conditions and additives on the resulting structure, shape, and physical properties of the crystals. For the last decade, our group, as well as others, , have shown that calcite and vaterite, two of the anhydrous polymorphs of CaCO 3 , can incorporate both organic and inorganic additives. Specifically, it was demonstrated that the building blocks of proteins and polysaccharides, namely, amino acids (AAs) ,, and monosaccharides (MSs), respectively, can be incorporated into the crystal lattice of the host, and induce changes in its lattice parameters.…”
Section: Introductionmentioning
confidence: 88%